Ultrafast, Non‐Equilibrium and Transient Heating and Sintering of Nanocrystals for Nanoscale Metal Printing. Issue 50 (7th October 2021) - Podder, Chinmoy; Gong, Xiangtao; Pan, Heng
Abstract: The carrier excitation, relaxation, energy transport, and conversion processes during light‐nanocrystal (NC) interactions have been intensively investigated for applications in optoelectronics, photocatalysis, and photovoltaics. However, there are limited studies on the non‐equilibrium heating under relatively high laser excitation that leads to NCs sintering. Here, the authors use femtosecond laser two‐pulse correlation and in‐situ optical transmission probing to investigate the non‐equilibrium heating of NCs and transient sintering dynamics. First, a two‐pulse correlation study reveals that the sintering rate strongly increases when the two heating laser pulses are temporally separated by <10 ps. Second, the sintering rate is found to increase nonlinearly with laser fluence when heating with ≈700 fs laser pulses. By three‐temperature modeling, the NC sintering mechanism mediated by electron induced ligand transformation is suggested. The ultrafast and non‐equilibrium process facilitates sintering in dry (spin‐coated) and wet (solvent suspended) environments. The nonlinear dependence of sintering rate on laser fluence is exploited to print sub‐diffraction‐limited features in NC suspension. The smallest feature printed is ≈200 nm, which is ≈¼ of the laser wavelength. These findings provide a new perspective toward nanomanufacturing development based on probing and engineering ultrafast transport phenomena in functional NCs. Abstract : Conventional thermal sintering of nanoparticles occurs on a nanosecond scale or longer. In this article, laser nanocrystal sintering process with characteristic time on a picosecond scale is reported. The process enables direct, polymer‐free and high‐precision metal printing which has been challenging to achieve up to date. The smallest feature printed is ≈200 nm, which is ≈¼ of the laser wavelength.